Exoskeleton-assisted upper limb rehabilitation after stroke: a randomized controlled trial - AKGÜN, İREM; DEMİRBÜKEN, İLKŞAN; TİMURTAŞ, EREN; POLAT, MİNE GÜLDEN (My University, 2024)
Objectives: The upper-limb exoskeleton training program which is repetetive and task-specific therapy can improve motor functions in patients with stroke. To compare the effect of an upper-limb exoskeleton training program with Bobath concept on upper limb motor functions in individuals with chronic stroke. Methods: Participants were randomly assigned to exoskeleton group (EG, n = 12) or to Bobath group (BG, n = 12). Interventions were matched in terms of session duration and total number of sessions and performed 2 times per week for 6-weeks. Primary outcome was Fugl-Meyer- Upper Extremity (FMA-UE). Secondary outcomes were Modified Ashworth Scale (elbow and wrist flexor muscles), Motor Activity Log-30 which is consist of two parts as an amount of use (AOU) and quality of movement (QOM), and The Nottingham Extended Activities of Daily Living (NEADL) index. Results: After 12-sessions of training, the mean (SD) FMA-UE score increased by 5.7 (2.9) in the EG, and 1.9 (1.5) points in the BG (p <.05). In total, 40% of participants (5/12) demonstrated a clinically meaningful improvement (≥5.25 points) in the FM-UE, while none of the participants reached MCID score in the bobath group. Changes in the AOU, QOM, and NEADL were significantly larger in the EG compared to BG (p <.05). 7/12 (58.33%) of participants for AOU and 5/12 (42%) of participants for QOM in the EG showed that clinically meaningful change. 5/12 of participants (42%) in the EG demonstrated ≥4.9-point increase in NEADL score. Discussion: High-intensity repetitive arm and hand exercises with an exoskeleton device was safe and feasible. Exoskeleton-assisted training demonstrated significant benefits in improving upper limb functions and quality of life in individuals after stroke.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Yaşam Bilimleri; Nöroloji (klinik); Life Sciences; Neurology (clinical); Bobath; exoskeleton; motor function; Stroke rehabilitation; upper extremity